PERAN MAJELIS TAKLIM DAN SHOLAWAT DIBA KUBRO SEBAGAI SARANA PENDIDIKAN AGAMA ISLAM DI MASYARAKAT JOGOROTO - Muammar, Adam; Jumari, Jumari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The role of Majelis Taklim and Sholawat Diba Kubro as a medium of Islamic religious instruction in the community of Jogoroto District, Jombang Regency. This study utilized a qualitative method featuring a field research framework. Data were gathered via observation, comprehensive interviews, and documentation. The study participants included the majelis management, religious leaders, and community members involved in the activities. The findings reveal that Majelis Taklim and Sholawat Diba Kubro play an important role as non-formal Islamic educational media through the delivery of Islamic teachings, habituation of worship practices, moral development, and strengthening social solidarity within society. The Islamic educational values embedded in these activities include faith, worship, morality, Islamic brotherhood, tolerance, and social responsibility. The effects of these actions are reflected in the heightened religious awareness within the community, the growth of worship awareness, and the establishment of harmonious social relationships among residents. Keywords: Majelis Taklim, Sholawat Diba Kubro, Islamic Religious Education, Community..